Hierarchical N/P-Co-Doped Porous Carbon as Host Materials for High-Performance Lithium Sulfur Battery. Issue 6 (15th March 2019) - Luo, Jiangbin; Dong, Yue; Xiaoqin, Huiqiang; Liu, Hang; Rao, Xianfa; Zhong, Shengwen; Liu, Ruiping
Abstract : Lithium-sulfur battery (LSBs) is one of the most promising energy storage technologies due to its high energy density. The insulating properties of the sulfur and shuttle effect of the polysulfides during charge/discharge process limit its commercial application. In this work, we prepared a hierarchical N/P co-doped porous carbon (DPC) via NH4 H2 PO4 and KHCO3 dual-activation of the porous carbon, which was obtained by annealing of nano-calcium carbonate/sucrose composites. The resulting DPC/S composite as cathode materials for LSBs shows a promising long-term cycling stability (968.9 mAh g −1 after 100 cycles at 0.2 C) and rate performance (624.4 mAh g −1 at 1 C, 545.4 mAh g −1 at 2 C). The structural superiority of DPC host materials, i.e., highly porous structure, hierarchical pores and N/P co-doping contributes to the superior electrochemical performance of the materials. The simple synthesis process and low cost of the highly porous carbon makes it a promising candidate for encapsulation of active sulfur in lithium sulfur battery.